Radio-frequency connectors. Sectional specification for RF coaxial connectors with 5 mm inner diameter of outer conductor, with quick-lock- or screw-coupling, characteristic impedance 50 O (series 2, 2-5) Part 66, (8th April 2021) - British Standards Institution,
No abstract available